Microplastic pollution in the food web: observation of ingestion by the talitrid amphipod Cryptorchestia garbinii on the shores of Lake Garda. Issue 1 (11th July 2023) - Battistin, G.; Latella, L.; Iannilli, V.
Abstract: Plastic pollution in the environment has become a much-discussed issue worldwide. In recent decades, the contamination of all environments has become increasingly evident, in particular, that of water is highly concerning. Ingestion by different animal species under natural conditions has also been demonstrated. Among these is the Talitrid Amphipod Cryptorchestia garbinii, which lives on the banks of the internal waterways and lakes' shorelines. As detritivores species, it is very exposed to microplastics that can be ingested, probably mistaking them for food. Aiming to highlight the microplastic ingestion and the role of this species as an entry point for the food web, we analyzed 80 specimens from 4 sites along the shores of Garda Lake, one of the first lakes in Italy to be studied for this type of contamination. The microplastics ingested were observed and quantified through the Nile Red staining method. We were able to verify the presence of ingested microplastics in all the samples analyzed and, therefore, in the food web. This species could serve as valuable natural models of plastic exposure. Microplastic sentinel species can be used as a proxy for environmental exposure and ecosystem monitoring tools to quantify and assess the impacts of microplastic contamination.